40Ar–39Ar ages from the Sabongari and Nana igneous complexes within the central part of the Cameroon Line (Central Africa). (November 2018) - Njonfang, Emmanuel; Laurenzi, Marinella A.; Nguet, Pauline Wokwenmendam; Cozzupoli, Domenico
Abstract: The Sabongari and Nana volcano–plutonic complexes are two of about sixty complexes that outcrop along the Cameroon Line. In both complexes, granites and rhyolites are the prevalent rock types among plutonic and volcanic rocks, respectively. The Nana complex has never been dated, while data ranging from 77 to 49 Ma have been reported for the Sabongari intrusive rocks. These ages appeared inconsistent with field relationships, the oldest ones 77 and 74 Ma being obtained on microgranites that form a WSW–ENE alignment of small plugs within the main granite. We performed 40 Ar– 39 Ar laser step–heating analyses on a plutonic and a volcanic rock for each complex. The age obtained on Sabongari granite, 57.70 ± 0.44 Ma, is about 1 Ma older than the age obtained on a related trachyte, and consistent with field relationships. Rocks from the Nana complex are younger than those from Sabongari, ranging from 52 to 49 Ma. This is the second paper with 40 Ar– 39 Ar data on the Cameroon Line anorogenic complexes after that on the Hossere Nigo complex, sited at about 240 km to the NE of the study area. Both results challenge earlier K–Ar and Rb–Sr model ages along the Cameroon Line. More 40 Ar– 39 Ar data on a large number of complexes are necessary to better understand their spatial relationships over time. Highlights: The Sabongari and Nana complexes belong to the central part of the Cameroon Line. They are for the first time dated using 40 Ar– 39 Ar method. Ages range from 57.70 to 56.70 Ma at Sabongari to 52–49 Ma at Nana. The Nigo complex, about 240 km to the NE, is older (65 Ma). Any discussion on their spatial relationships over time needs more 40 Ar– 39 Ar datings.